Surfactant-free gelatin-stabilised biodegradable polymerised high internal phase emulsions with macroporous structures - Furmidge, Rachel; Jackson, Caitlin E.; Velázquez de la Paz, María Fernanda; Workman, Victoria L.; Green, Nicola H.; Reilly, Gwendolen C.; Hearnden, Vanessa; Claeyssens, Frederik (Frontiers in Chemistry, 2023)
High internal phase emulsion (HIPE) templating is a well-established method for the generation of polymeric materials with high porosity (>74%) and degree of interconnectivity. The porosity and pore size can be altered by adjusting parameters during emulsification, which affects the properties of the resulting porous structure. However, there remain challenges for the fabrication of polyHIPEs, including typically small pore sizes (~20-50 μm) and the use of surfactants, which can limit their use in biological applications. Here, we present the use of gelatin, a natural polymer, during the formation of polyHIPE structures, through the use of two biodegradable polymers, polycaprolactone-methacrylate (PCL-M) and polyglycerol sebacate-methacrylate (PGS-M). When gelatin is used as the internal phase, it is capable of stabilising emulsions without the need for an additional surfactant. Furthermore, by changing the concentration of gelatin within the internal phase, the pore size of the resulting polyHIPE can be tuned. 5% gelatin solution resulted in the largest mean pore size, increasing from 53 µm to 80 µm and 28 µm to 94 µm for PCL-M and PGS-M respectively. In addition, the inclusion of gelatin further increased the mechanical properties of the polyHIPEs and increased the period an emulsion could be stored before curing. Our results demonstrate the potential to use gelatin for the fabrication of surfactant-free polyHIPEs with macroporous structures, with potential applications in tissue engineering, environmental and agricultural industries.